Grammatical Errors Made by the Students During Seminar Proposal Examination - Robi Soma (Didascein : Journal of English Education, 2023)
Those proficient in spoken English grammar can adequately grasp the English language. This ability differs significantly from written English grammar since it occurs naturally and spontaneously during conversations without any preparation. This study examined spoken grammatical errors committed by English major students during the seminar proposal examination at one public university in Jambi. To carry out this study, the researcher utilized case study research. This research effort enlisted the participation of five students from the eighth and tenth semesters of an English education study program, one male and four females. The researcher classified the grammatical errors based on Richard’s theory (1990) as (1) Errors in the production of verb groups, (2) errors in the distribution of verb groups, (3) miscellaneous errors, (4) errors in the use of prepositions, (5) errors in the use of articles, and (6) errors in the use of the question. The spoken grammatical errors were assessed using the six categories above after listening, audiotaping, and transcribing their seminar proposal assessment. The findings and discussion sections will go through each feature type in further detail. The researcher expected to get some distinct information in relation to students’ spoken grammatical errors and make some improvements through teaching and learning developments.